PENGARUH KOMPETENSI, LINGKUNGAN KERJA DAN MOTIVASI KERJA PEGAWAI TERHADAP SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN KEPULAUAN SELAYAR - Sri Astuty -; Ahmad Firman; Mustaking Mustaking (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2021)
This study aims to determine and analyze (1) the effect of competence, work environment, and work motivation toward the employee performance at the Civil Service Police Unit and Firefighter in Selayar Regency (2) the most dominant variable affects the employee performance at the Civil Service Police Unit and the Firefighter of Selayar Islands. This study approach used a quantitative study that was conducted at the Civil Service Police Unit and the Firefighter in Selayar Regency in July 2020. The study population was all employees of the Civil Service Police Unit and Firefighter of Selayar Islands by 421 people. The sample selection in this study was implemented using the simple random sampling method, namely taking the sample members from the population at random without paying attention to the strata in the population. The total sample was 81 employees. The results show that (1) there is a positive and significant effect of competence toward the employee performance of the Civil Service Police Unit and Firefighter of the Selayar Islands Regency (2) there is a positive and significant of work environment toward the employee performance of the Civil Service Police Unit and Firefighter of the Selayar Islands Regency (3) there is a positive and significant effect of work motivation partially toward the employee performance at the Civil Service Police Unit and the Firefighter (4) there is a positive and significant effect on motivation simultaneously toward the employee performance at the Civil Service Police Unit and the Firefighter in Selayar Islands (5) work motivation is the most dominant variable affects the employee performance of the Civil Service Police and Firefighter of the Selayar Islands Regency.